Simulation Parameter Test and Seepage Effect Analysis of Pile-Anchor Support for Binary Slope - Xuhe Gao; Weiping Tian; Zhipei Zhang; Jiachun Li; Hongliang Qi (Advances in Civil Engineering)
It is a difficult point in the field of geotechnical engineering to test the simulation parameters of the pile-anchor supporting structure of slope excavation and analyze the effect of seepage on the stress of the structure. This study relies on the right side slope treatment project of a highway in Guizhou Province. Aiming at the defect that the current numerical simulation parameter selection is fuzzy, the deep displacement monitoring data and P value inspection method are used to check the simulation parameters. We establish a 2D finite element model of slope excavation and support. The superposition calculation method of pore water pressure was used to analyze the stress characteristics of the slope-supporting structure after applying steady-state seepage. The analysis shows the following. ① Initial support stage: the steady-state seepage causes the axial force extreme value of the prestressed anchor cable to increase by 11.22% at this stage. ② Secondary support stage: the steady-state seepage reduces the shear limit of the antislide pile by 3.11% and the bending moment by 14.90%. ③ Comparative analysis of the two supporting phases: the newly constructed pile-anchor supporting structure has a significant effect on the original pile-anchor supporting structure. At the same time, the bending and shearing resistance of the newly added antislide piles has not been fully exerted. The research results provide new ideas for the research on the safety control ability of the slope support construction process.